Landmark Kota Dalam Pandangan Masyarakat - prasetya, edhi; Prawesthi, Ashri; S. Sadana, Agus; Anggita, Diptya; Ibnu Wibisono, Adryanto; Dewanto, Wahyu (Institut Teknologi Nasional Yogyakarta, 2024)
Program of Pengabdian Kepada Masyarakat (PKM) is a Community Service Program aims to enhance public understanding of the role and significance of city landmarks, particularly the Tugu Pal Putih in Yogyakarta, within the context of urban spaces and cultural heritage. The range of activities were conducted using two methods: 1) offline distribution of cups and plates featuring landmark-related imagery and text, and 2) online dissemination through short videos on social media platforms such as Instagram and TikTok. The program also involved students as part of the team. The results showed: 1) an increased public awareness of the philosophical and historical values of Tugu Pal Putih, 2) a deeper understanding of the role of landmarks in the structure of urban spaces, and 3) a heightened awareness of the importance of preserving landmarks as part of world cultural heritage. The chosen media proved effective in reaching various segments of the public, both locally and regionally, and successfully encouraged greater community involvement in preserving and promoting city landmarks.